THE GACOAN EFFECT: COMPETITIVE ADVANTAGE AND SOCIAL DINING IN BEKASI - Angelli Oktavia; Devi Medyani Cahya; Zanvika Triani (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
This study investigates the persistent crowding phenomenon at Mie Gacoan in Bekasi, a densely populated satellite city. The research purposes are to identify the behavior triggers of customer retention and understand the consumer experience from an immersive perspective. Adopting a qualitative approach, the methodology integrates direct observation of spatial dynamics and participant observation across four strategic branches (Juanda, Golden City, Bintara and Harapan Indah), where researchers actively engaged in the purchasing and dining journey. The main findings reveal that the continuous crowds are driven by a strong “social proof” effect amplified by visible queues alongside the restaurant’s successful adaptation as an affordable “third place” for suburban youth socialization. Consumers willingly endure long waiting times because the shared queueing and dining experience serves as a form of lifestyle validation. The business implication suggests that for low-cost food enterprises in suburban markets, atmospheric and social value are just as critical as pricing strategies for sustaining hyper-growth.